Legal Protection to Victims of Criminal Acts in Efforts to Realize Restorative Justice - Timomor, Adensi (International Journal of Psychosocial Rehabilitation, 2020)
One party that really needs protection in a crime is a victim of crime. The important role of the victim is to be given attention and protection because the victim is the most disadvantaged party in the occurrence of a crime, so services and protection must be given to him/her. The Indonesian criminal justice system basically provides legal protection for victims of criminal acts but is still very minimal compared to the protection of the rights of the suspect or defendant. Various laws and regulations, specifically in the field of criminal acts, have provided regulations regarding the protection of the rights of victims of crime. Protection and assistance for victims of crime is an urgent and important thing to immediately implement. This research was conducted with a conceptual and a legal approach. This research is a type of normative research using data sources, namely literature and documents, which are primary legal materials. The results of the study indicate that the regulation of legal protection against victims of criminal acts has been regulated in the Criminal Code but is still very minimal and has also been regulated in a number of special laws but still regulates in a concise and abstract manner and has not explicitly and specifically placed victims of crime as part of the criminal justice system.